Isolation and identification of bacterial protease enzyme of leather waste - Pertiwiningrum, A.; Anggraini, F. D.; Fitrianto, N. A.; Rochijan, R. (Diponegoro University, 2017)
The objectives of this study were to isolate and identify bacteria which produced protease enzyme from liquid and solid waste of tannery, and their characterization of enzymatic activities. The bacterial isolation used a sample of liquid and solid waste from leather waste which taken from a different waste reservoirs (three liquid waste and one solid waste in unhairing phase). Data of the isolated bacteria, OD 600 nm bacterial growth, the identification of bacteria, and enzyme precipitation with 60% ammonium sulfate were analyzed descriptively. The colony diameter, diameter of clear zone, proteolytic index, and enzymatic activities characterization on difference of pH and temperature were analyzed using Completely Randomized Design, followed by Duncan’s New Multiple Range Test. The second sample from four samples of the isolated bacteria was tested further for their proteolytic activity. The morphology of the colony was circle, white, flat ledges and convex elevation, the basal cell morphology was red, gram-negative, non-motile, catalase positive and gelatin negative. The highest activity of enzyme on pH 11 with activity unit enzyme 45,18±1,77 U/ml and specific enzyme activity 43,19±1,69 U/mg and temperature of 40°C activity unit enzyme 54,02±1,89 U/ml and specific enzyme activity 51,65±1,8 U/mg. The activity of enzyme from protease were precipitated ammonium sulfate 60% showed a higher result of (75,8 U/ml) rather than rough protease.